A Rare Complication of Insulin Therapy in a Child with Newly Diagnosed Type 1 Diabetes: Insulin Edema - Sezer Acar (Galenos Yayinevi, 2021)
Although insulin therapy has a critical role in the management of patients with type 1 diabetes, it may cause various side effects at varying rates. Insulin edema is a very rare complication that is mostly associated with the initiation of insulin therapy in patients with newly diagnosed diabetes or the intensification of insulin therapy in those with poor glycemic control. Its clinical spectrum ranges from mild peripheral edema to severe serosal effusions (peritoneal, pleural and pericardial) and heart failure. Although it has been known about for a long time, only a small number of cases have been reported on so far and its incidence is not clear. Additionally, most cases are thought to be undiagnosed due to its mild clinical presentation. Here, we present a 10-year-old male with type 1 diabetes who developed insulin edema following insulin therapy and improved spontaneously with fluid/salt restriction. In conclusion, it should be kept in mind that there is a possibility of the development of insulin edema after the initiation of insulin therapy in patients with diabetes.